EXTRUDED PRODUCT WITH BLACKBERRY SEED BY-PRODUCT: ECO-FRIENDLY SUSTAINABLE APPROACH TO UTILIZE BIOACTIVE COMPOUNDS - Ravula Bharathi, Aruna Mesa, I.V. Lalitha Kumari, P. Josthna, D. Sheela Paul (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
The exponential population growth and increasing consumer demands for healthy functional foods lead to the dire need for exploration of sustainable phytochemical rich sources. In-depth research on zero-waste food processing through food by-product utility may occupy a promising solution as an eco-friendly method through minimizing the environmental adverse consequences associated with the disposal of food waste. Extruded snack food products being efficient in producing wide variety of innovative value addition and contributes valorization to the agro-industrial waste. Murukku, the traditional Indian savoury is an extruded product suitable to incorporate dehydrated functional food waste powders as appropriate tool for effective bioactive compounds utilization. Blackberry seeds are one of the healthy choices among food waste by-products being rich in antioxidants, dietary fiber, phenolic compounds offering significant nutritional and health benefits to reduce the incidence of chronic disease conditions. Based on this background, the current investigation was aimed at the development of black berry seed based extruded product in the form of murukku. Three different trials were formulation with the major ingredients as rice flour, besan flour, black gram dhal, moong dhal and blackberry seed powder. They were subjected to organoleptic evaluation to test the acceptability of the formulated trials. The panel mean organoleptic scores indicated high acceptability for the portioning of 40:20:20:5:15 in the respective major ingredients. The findings well demonstrated the blackberry seed based murukku as nutritious ready to eat snack owing to good source of protein, fat, crude fiber, calcium and iron. Being low in moisture content might be beneficial in extending shelf stability of the product and ensures quality and safety of the product due low water activity in the product. Promotion of such bioactive food by-products may be an invaluable approach to mitigate protein energy malnutrition in the children and chronic diseases among adults as well as to target for public health and sustainable development goals.